Dai Nippon Forced Labor Politics, 1943-1945: Romusha Rendezvous at Muaro Sijunjung Lane, Sijunjung Regency - Fikrul Hanif Sufyan; Zusneli Zubir; Refisrul; Rita Novita (Paramita: Historical Studies Journal, 2025)
Abstract: The regime changes from the Dutch Colonial to the Dai Nippon government initially brought good news for the movement leaders. However, within 3,5 years of its reign, it brought suffering to the Indonesian people. This article aims to analyze the process of Japanese entry into Indonesia, describe the beginning and course of the Romusha policy in Indonesia, and analyze the impact of the Dai Nippon government's miserable forced labor along the Muaro Sijunjung route.  This article uses historical methods, including heuristics, criticism, interpretation, and historiography. One of the Dai Nippon government's policies towards society was the Romusha. The massive work of building a mass transport line connecting the point of Muaro Sijunjung to Pekanbaru and the ports on the East Coast of Sumatra was massive, requiring hundreds of human beings.  The massive recruitment of human labor was carried out using various strategies and the propaganda of movement figures. The inhumane treatment and killing of Romusha workers were one of the various treatments they received from 1943 to 1945 in Muaro Sijunjung, West Sumatra. Abstrak: Pergantian rezim dari Kolonial Belanda kepada pemerintah Dai Nippon, awalnya membawa kabar gembira, untuk kalangan tokoh pergerakan. Namun, dalam 3,5 tahun masa pemerintahannya, justru membawa penderitaan untuk rakyat Indonesia. Artikel ini bertujuan untuk menganalisis proses masuknya Jepang ke Indonesia, menguraikan awal dan jalannya kebijakan Romusha di Indonesia, dan menganalisis dampak kerja paksa pemerintah Dai Nippon yang menyengsarakan sepanjang rute Muaro Sijunjung.  Artikel ini disusun dalam metode sejarah, yang terdiri dari heuristik, kritik, interpretasi, dan historiografi. Satu dari sekian kebijakan pemerintah Dai Nippon terhadap masyarakat adalah Romusha. Pekerjaan besar-besaran membangun jalur transportasi massal yang menghubungkan titik Muaro Sijunjung menuju Pekanbaru dan pelabuhan di Pantai Timur Sumatra, adalah pekerjaan massal–yang membutuhkan ratusan manusia. Untuk merekrut besar-besaran tenaga manusia itu, dilakukan dengan beragam strategi dan melalui propaganda tokoh-tokoh pergerakan. Perlakukan yang tidak manusiawi dan pembunuhan terhadap tenaga Romusha adalah satu dari bermacam perlakuan yang diterima mereka sejak 1943-1945 di Muaro Sijunjung, Sumatra Barat.